Determinants of Carbon Emissions Levels in Indonesia (Efficient: Indonesian Journal of Development Economics, 2022)
This study aims to analyze the effect of population growth, economic growth, energy consumption, and growth in the number of vehicles on carbon emissions in Indonesia. This study uses data in Indonesia in 1986—2019. The method used is multiple linear regression analysis with Error Correction Model (ECM) approach. The results of this study indicate that in the short term there is no independent variable that has a significant effect on carbon emissions. In the long term, population growth has a significant negative relationship with carbon emissions. Economic growth and energy consumption have a significant positive relationship to carbon emissions, meanwhile growth in number of vehicles has no significant relationship to carbon emissions. Penelitian ini bertujuan untuk menganalisis pengaruh dari pertumbuhan penduduk, pertumbuhan ekonomi, konsumsi energi, dan pertumbuhan jumlah kendaraan terhadap emisi karbon di Indonesia. Penelitian ini menggunakan data di Indonesia pada tahun 1986—2019. Metode yang digunakan adalah analisis regresi linier berganda dengan pendekatan berupa Error Correction Model (ECM). Hasil dari penelitian ini menunjukkan bahwa dalam jangka pendek tidak ada variabel independen yang berpengaruh signifikan terhadap emisi karbon. Dalam jangka panjang, pertumbuhan penduduk memiliki hubungan negatif signifikan dengan emisi karbon. Pertumbuhan ekonomi dan konsumsi energi memiliki hubungan positif signifikan terhadap emisi karbon, sedangkan pertumbuhan jumlah kendaraan memiliki hubungan yang tidak signifikan terhadap emisi karbon.